Kata Sapaan Sebagai Penanda Sosiolek Dalam Terjemahan Novel Burung-Burung Manyar Karya Yb. Mangunwijaya Oleh Megumi Funachi - Kasmawati Kasmawati (Diponegoro University, 2021)
The purpose of this study is to analyze the translation of greeting words in Indonesian to Japanese, especially greeting words as a mark of sociolect. The resources used in this study are the novel of Burung-Burung Manyar by Y.B Mangunwijaya and its translation, Arashi no Naka no Manyaru by Megumi Funachi. The data identified in this novel as much as 176 data but the author only analyze 48 data. The theory used in this study are greeting words theory from Harimurti Kridalaksana (1982) and Sociolinguistic theory from Sumarsono and Paina Partana (2002). The approach used in this study is a sociolinguistic approach with a qualitative descriptive method. The result of this study shows that social factors, gender, and age influence the use of greeting words as mark of sociolect.